2021
DOI: 10.7759/cureus.13561
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Atherosclerosis in Patients With Autosomal Dominant Polycystic Kidney Disease

Abstract: In this study, we aimed to determine the endothelial dysfunction (ED) and atherosclerosis in patients with autosomal dominant polycystic kidney disease (ADPKD). Materials and methods This study was conducted with 83 subjects (26 male, mean age: 46±11 years) consisted of three groups including ADPKD, hypertension (HT) and healthy control groups. The groups were evaluated in terms of serum endocan and asymmetric dimethylarginine (ADMA) levels, flow-mediated dilatation (FMD), nitroglycerin-mediated dilation (NMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated elevated plasma endocan levels in polycystic kidney disease, immunoglobulin A nephropathy, chronic kidney disease, and hypertension (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated elevated plasma endocan levels in polycystic kidney disease, immunoglobulin A nephropathy, chronic kidney disease, and hypertension (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 96%
“…Endocan combined with angiopoietin-1 and HF-1a could be emerging biomarkers for patients at the early stages, having potential utility for the assessment of the disease progression. Recently, Ekinci et al conducted a study with 51 ADPKD and 20 hypertensive patients to evaluate endothelial dysfunction and atherosclerosis in terms of endocan, ADMA levels, flow-mediated dilatation (FMD), nitroglycerin-mediated dilation (NMD), and carotid intima-media thickness (CIMT) [ 78 ]. Although no significant difference was found in serum endocan levels between ADPKD and hypertensive patients, in ADPKD patients with eGFR≤60 ml/min/1.73 m 2 , serum endocan levels were significantly higher than those in patients with eGFR>60 ml/min/1.73 m 2 .…”
Section: Endocan and Kidney Diseasesmentioning
confidence: 99%
“…Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a common monogenic disorder with an increasing prevalence in the last decade [1,2]. The patients affected by ADPKD are characterized by progressive formation of cysts in the kidneys with progressive renal failure; in addition, more than half suffer from an increased predisposition to atherosclerosis, chronic inflammation, and show a higher risk of cardiovascular disease [3]. Although a fully reliable disease marker is still missing, several biochemical markers that can be assayed in patients' blood and urine such as albumin, creatinine and total proteins [4].…”
Section: Introductionmentioning
confidence: 99%